World and National Trends in University Libraries Acquisition - Irina K. Razumova; Alexander Yu. Kuznetsov (National Research Mordova State University, 2018)
Introduction. We investigated the problem of comparative analysis of the world and national trends of development of information support of the university research and education and position of Russia in the world academic community. Materials and Methods. We analyzed international and national surveys with data processing methods. Materials comprise results of the latest survey of the Publishers Communication Group, initial data of annual surveys conducted by Russian National electronic information consortium and the data of the surveys conducted by the Ministry of education and science of the Russian Federation in 2016 and 2017. Results. More than 90 % of world and Russian universities report of acquisition of scholarly resources via university consortia, 75 % of university funds are spent on periodicals. All peer groups demonstrate gradual migration to e-resources. In 2016, e-resources comprised 91 % of total acquisition expenses and e-books - 63 % of book acquisition. In Russia, more than 85 % of expenses on scholarly information belong to universities. From 2006 to 2014 average annual expenses on e-resources in Russian universities increased, however since the 2014, due to the economic crisis one can see shrinking of library expenses. This leads to a decrease in a number of acquired resources. Acquisition budgets of Russian leading universities (group 1) exceed budgets of non-leading universities (group 2) by ten times. In 2015, Russian universities spent 57 % of their acquisition budgets on the Elsevier databases. Discussion and Conclusions. Information support at Russian and world universities show common trends and features. The data on the e-resource expenses can be used as indicator of research activity in Russian institutions. It can also affect the information providers and scholarly journal publishers in development of the marketing, subscription and pricing policy in Russia.